Frequency of Vaginal Candidiasis amongst Pregnant Women: A Cross-Sectional Study (Medical Forum Monthly, 2020)
Objective: This study evaluated the frequency of vaginal candidiasis among pregnant women.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Antenatal Care Clinic Sheikh Zaid Hospital Larkana from February 2019 to June 2020.Materials and Methods: A total of 384 pregnant women were including in the study at High vaginal swabs were taken from these women for gram staining and culture to diagnosis the candidiasis.Results: A total of 384 samples of pregnant women were examined, 216 were positive, the frequency of vaginal candidiasis showed 56.2%. The age group 21 to 30 years showing the highest number 133(61.6%) of positive candidiasis. Multigravida 188(87%) was more commonly affected than primigravida 28(13%) and commonly seen in the third trimester 136(63.0%).Conclusion: In the study, a very high frequency of vaginal candidiasis was observed among women, so there is a keen need for related health education programs for awareness, besides effective antennal care system for early diagnosis/screening as well as prompt treatment of vagina candidiasis in pregnant women.